Curriculum Development In SMPN 1 Kramatwatu - Panji Ginanjar (Journal of English Language Teaching and Cultural Studies, 2019)
This research intends to analyze about the 2013 Curriculum Learning Implementation in SMPN 1 Kramatwatu. This study is a qualitative research with the intent to collect process, analyze, and present the data objectively about the curriculum development in SMPN 1 Kramatwatu. The researcher conducts an observation and interview to collect the data. The result concludes that the school has been considered ready to run the 2013 curriculum with some readiness that has been implemented. The implementation of learning has also been going well in accordance with the applicable curriculum, namely the 2013 curriculum. The school has been able to become a pilot project in the implementation of the 2013 curriculum with school readiness, complete facilities and infrastructure, and teachers have mastered the 2013 curriculum.